DOP59 What is the relationship between fatigue, pain and urgency in people with inflammatory bowel disease? Results of the IBD-BOOST survey in 8486 participants. (30th January 2023) - Hart, A; Miller, L; Hamborg, T; Stagg, I; McGuinness, S; Wileman, V; Tzorovili, E; Mihaylova, B; Roukas, C; Aziz, Q; Czuber-Dochan, W; Dibley, L; et al.
Abstract: Background: Fatigue, pain and faecal incontinence are common in people with IBD. However, little is known about co-existence of these multiple symptoms, how they inter-relate and whether people want help for these symptoms. In qualitative interviews, patients have reported that these symptoms are often ignored in clinical consultations, where the focus is on inflammation, but that they are very bothered by these symptoms, even when disease is apparently in remission. The aim of this study was to determine the presence and relationship between fatigue, pain and incontinence in people with inflammatory bowel disease, and desire for intervention for these symptoms. Methods: A purpose-designed survey (online or postal), incorporating validated tools and demographic details, was sent to unselected UK clinic and UK IBD-BioResource adult patients. When the covid-19 pandemic halted clinic recruitment, additional self-selected UK recruits were solicited via social media. Using the validated PROMIS tools, the following definitions were used for presence of symptoms: fatigue: PROMIS fatigue T-score of 60 or more; pain: PROMIS pain intensity T-score of 60 or more; PROMIS bowel incontinence: raw score of 50 or more. Participants also reported disease activity using the relevant PRO-2 score, IBD-Control, anxiety (GAD-7), depression (PHQ-9) and quality of life (EQ-5D-5L) which will all be reported elsewhere. Results: A total of 8486 useable responses were received (7716 online, 770 postal). 4176 reported Crohn's disease, 4255 had ulcerative colitis or other form of IBD. There were 3281 men and 4883 women. Median age was 51 years (range 18 - 92). 2550 (30%) reported fatigue, 1766 (21%) pain and 4565 (54%) faecal incontinence according to the above definitions; 925 (10.9%) reported having all three symptoms. Demographics by symptom are shown in Table 1. Table 2 reports those participants indicating the presence of each symptom and each combination of symptoms. Table 3 shows a summary of self-defined severity and impact of symptoms (scoring scale 0-10 for both severity and impact of each symptom). Participants scored severity and impact a mean between 3.3 and 4.8, with a wide variation. 56% of all respondents (not just those with symptoms) "definitely" wanted help for fatigue; 42% wanted help for pain; 53% wanted help for incontinence. 29% reported "definitely" wanting help for all three symptoms (Table 4). Conclusion: This study confirms that fatigue, pain and urgency are common in IBD and for the first time reports the co-existence and unmet need for help with these symptoms.